PENGARUH PEMBERIAN FEEDBACK DAN SELF EFFICACY TERHADAP HASIL BELAJAR IPA-KIMIA - HAIRIDA HAIRIDA (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2013)
The purpose of this research is to find out the effect of feedback giving and self efficacy toward the achievement in chemistry-science SMP by controlling the student’s intelligence. This research was conducted by employing and experimental method called 2 x 2 treatment by level design, and used analysis of covariate (ANCOVA) has been applied. After controlling the student’s intelligence, it was found that the achievement in chemistry science of the group which was given teacher feedback was higher than the group which was given peer feedback, and there was an interaction effect between of feedback giving and the self efficacy toward in chemistry-science SMP. Interaction effect is shown by the achievement in chemistry-science for students in the group given teacher feedback was higher than the group of students is given peer feedback, especially for student’s in the group that have high self efficacy. Otherwise, especially for student’s in the group that have lower self efficacy, the achievement in chemistry-science of the student’s in the group which was given teacher feedback was lower than the group which was given peer feedback. The results of this study concluded that the results of studying science-chemistry as a whole is affected by the type of giving feedback and high and low self-efficacy students. To that end, students need to be self efficacy considerations in determining ways of giving the right feedback.